Faktor Penentu Pengambilan Keputusan untuk Wakaf Uang Secara Online pada Generasi Milenial - Nashir, Fathin Kemala; Huda, Nurul; Indra (Badan Wakaf Indonesia, 2023)
The realization of cash waqf is currently still very limited. Waqf literacy is still very minimal, especially for millennials. The millennial generation is a generation that is very close to technology, judging from the daily life of millennials, it is very closely related to activities carried out with technology. Factors that affect the online cash waqf generally previous researchers limited only to a few factors such as some discussing only limited to Social Influence (SI), and Religiosity or factors of Knowledge, Belief, Religiosity, Attitude, Subjective Norms and Perceived Behavioral Control (PBC). This study aims to analyze the influence of perceived usefulness, perceived ease of use, religiousity, trust, social influence, information, attitude, subjective norm, perceived behavioral control, and waqf literacy on the intentions or desires of millennials to do online cash waqf. The data analysis method in this study uses the Structural Equation Model – Partial Least Squares (SEM-PLS). The research sample used in this study was the millennial generation who were born in the period from 1981 to 1996. The data used in this study was through field research, in this case data collection was carried out by distributing questionnaires that were distributed through online media (google form) to the millennial generation. The first result in this study is that perceived usefulness, religiousity, trust, social influence, information, attitude, perceived behavioral control greatly influence the millennial generation in making money online. While waqaf literacy, Perceived Ease of Use and Subjective Norm do not greatly affect millennials in online cash waqf.